2018
DOI: 10.1128/iai.00143-18
|View full text |Cite
|
Sign up to set email alerts
|

T Cell-Independent Gamma Interferon and B Cells Cooperate To Prevent Mortality Associated with Disseminated Chlamydia muridarum Genital Tract Infection

Abstract: CD4 T cells and antibody are required for optimal acquired immunity to genital tract infection, and T cell-mediated gamma interferon (IFN-γ) production is necessary to clear infection in the absence of humoral immunity. However, the role of T cell-independent immune responses during primary infection remains unclear. We investigated this question by inoculating wild-type and immune-deficient mice with CM001, a clonal isolate capable of enhanced extragenital replication. Genital inoculation of wild-type mice re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
15
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 58 publications
2
15
1
Order By: Relevance
“…Recently, Poston et al have shown that T cell-independent IFN cooperates with B cells to prevent lethal dissemination caused by a highly virulent C. muridarum strain CM001 (17). Our data add to previous findings by showing ex vivo IFN secretion on the surface of CD11b+ NK1.1+ cells, indicating that group 1 ILCs elicit protective function, as least in part, by their production of IFN in the absence of T cells.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…Recently, Poston et al have shown that T cell-independent IFN cooperates with B cells to prevent lethal dissemination caused by a highly virulent C. muridarum strain CM001 (17). Our data add to previous findings by showing ex vivo IFN secretion on the surface of CD11b+ NK1.1+ cells, indicating that group 1 ILCs elicit protective function, as least in part, by their production of IFN in the absence of T cells.…”
Section: Discussionsupporting
confidence: 85%
“…In contrast, nude mice and mice lacking MHC class II-restricted CD4 T cells shed persistent high levels of bacteria from the FRT without showing obvious signs of wasting (15)(16)(17). While a large body of evidence points to a role for Th1, but not other Th lineage cells in protective immunity against Chlamydia (14,(18)(19)(20)(21)(22)(23).…”
Section: Introductionmentioning
confidence: 99%
“…The heightened protective chlamydial-specific Th1 cytokines (IFN-g and IL-2) and CD4 + memory and effector T-cells produced after immunization of mice (SC and IN) corroborate reports of Th1 immune effectors that can clear a C. muridarum vaginal challenge (10,40). Indeed, the protective role of Th1 cytokines has directly been correlated with IFN-g-mediated Chlamydia killing by activating T-cells (43,44). In line with our observation, CD4 + T-cells driven-immune responses with pronounced IFN-g production are reportedly adequate for protection against C. muridarum infections in the genital tract (45)(46)(47).…”
Section: Discussionsupporting
confidence: 77%
“…CD4 T cells are likely the main source of IFN-γ in these scenarios since NK or CD8 T cell depletion during primary or secondary Cm infection causes only mildly increased bacterial burdens [24, [29], [48]. This might suggest that CD4 T cell production of IFN- γ to direct antibody class-switching is critical to preventing disseminated primary infection, and this notion is supported by a recent study [47]. The source of this protective IFN-γ is likely to be Tfh cells in the draining lymph node, a CD4 subset that has not been carefully studied in the context of Chlamydia infection.…”
Section: Introductionmentioning
confidence: 83%
“…In contrast IFN-γ-deficient mice shed low levels of bacteria from the FRT, while B cell-deficient mice clear Cm from the FRT completely [22] [33]. Both mice, however, develop severe concurrent systemic infection, indicating that IFN-γ and humoral responses may be necessary for containing disseminating infection [33, [46, [47]. CD4 T cells are likely the main source of IFN-γ in these scenarios since NK or CD8 T cell depletion during primary or secondary Cm infection causes only mildly increased bacterial burdens [24, [29], [48].…”
Section: Introductionmentioning
confidence: 99%